Aeroservoelastic modeling and analysis of a six-DOF hypersonic flight vehicle. (June 2016) - Zong, Qun; You, Ming; Zeng, Fanlin; Dou, Liqian
By using light-weighted material in hypersonic flight vehicle, the vehicle body can be easily deformed. The mutual couplings in aerodynamics, flexible structure and control system will result in aeroservoelasticity problem. Based on the six-DOF geometry of a hypersonic flight vehicle, this paper uses assumed modes method, Shock-Expansion theory and Piston theory to develop the structural elastic model and the aerodynamic model, with actuator incorporated, the open-loop aeroservoelastic model of a six-DOF HFV is established. In open-loop analysis, the response of the elastic coordinates to the tail rudder deflection and the frequency characteristic of the transfer function of the tail rudder deflection to the first elastic coordinate are studied. A high gain feedback controller is designed for the aeroservoelastic model, and closed-loop analysis is conducted based on this model. The simulations show the influence of the elastic motion on the aerodynamic forces and moments.